Web API design considerations for resolving inherent issues in web environment. (19th March 2010) - Teo, Hui Ming; Kadir, Wan Mohd Nasir Wan
The recent trend in web application development is moving towards exposing the service functionality through application programming interface (API). Many web-based services start to offer APIs to support application-to-application integration with their consumers on top of the web. The trend has raised the demand for average web developers to know how to design APIs for web-based services. In this paper, we summarise a list of inherent issues in the web that developers should pay attention to, describe how web architecture may help to resolve these issues, and suggest design considerations for web API design. In addition, we demonstrate an experimental design process through a case study to design web API for social bookmarking service.